Bridging the island : Brazilians' views of Spanish America and themselves, 1865-1912 - Preuss, Ori (Madrid : Iberoamericana ; Orlando : Iberoamericana Vervuert Publishing ; Frankfurt am Main : Vervuert, 2011)
Explores the interplay between Brazilian interpretations of the national Self and the Spanish-American Other during the critical years spanning the demise of slavery and monarchy.
The island of Brazil and Spanish America : first bridges, 1865-1888 -- The end of slavery and the hopeful beginnings of a Latin American consciousness in Brazil -- The end of the monarchy and the unwelcome Hispano-Americanization of Brazil -- Close encounters of the peripheral kind : Luso-Hispano-American interaction in the Age of Empire and the ideologization of "Latin America" -- Recreating the island, maintaining the bridges : Rio Branco, Spanish America, and the myth of paz e concórdia.
Includes bibliographical references and index.
Online resource; title from PDF title page (Digitalia, viewed January 5, 2018)
Keywords: National characteristics, Brazilian -- History -- 19th century; National characteristics, Brazilian -- History -- 20th century; National characteristics, Latin American -- History -- 19th century; National characteristics, Latin American -- History -- 20th century; Public opinion -- Brazil -- History; Brazil -- Relations -- Latin America; Latin America -- Relations -- Brazil; Latin America -- Foreign public opinion, Brazilian; Brazil -- Civilization; Brazil -- History -- 1889-1930.; Electronic books